Exploring the Electronic Properties of Ribonucleic Acids Integrated Within a Schottky-Like Junction - Talebi, Sara; Daraghma, Souhad; Ramesh, Subramaniam; Bhassu, Subha; Periasamy, Vengadesh (Springer, 2019)
Deoxyribonucleic acid (DNA), being the main biomolecule of life, has been studied extensively in terms of its electronic properties, charge transport mechanisms and potential use in nano-electronic devices. The ability of DNA to self-replicate, self-assemble and mediate charge transfer has made it an interesting molecule to multidisciplinary researchers. However, not much attention has been given to ribonucleic acid (RNA), which is an equally important biomolecule that shares some common features with DNA. Elucidation of RNA’s electronic behavior could provide more information regarding its electronic properties, potentially offering a new biomolecule for application in bioelectronics. In this work, RNA samples integrated within two metal electrodes were subjected to positive and negative bias potentials and their resulting current profiles were investigated. Interestingly, current rectification similar to electric field-induced semi-conductive behavior of conventional Schottky junctions was observed for all RNA samples tested, indicating highly characteristic RNA-specific Schottky profiles. A non-linear profile was observed from the current–voltage (I–V) characteristics of gold (Au)-RNA-Au structures showing resemblance to metal-DNA structures investigated previously. Various solid-state parameters such as turn-on voltage, shunt resistance, series resistance and ideality factor were also calculated to further understand the biomaterial’s solid-state behavior. These results successfully demonstrated the exciting observation of the semi-conductive-like behavior of RNA which could be utilized as a tool in molecular electronics. © 2019, The Minerals, Metals & Materials Society.